Study on the foaming tendency of ionic liquids of different anion and nmethyldiethanolamine (MDEA) for the removal of carbon dioxide - Thuraiya , Mohammad Thaim (2015)
The removal of acid gases especially CO₂ is highly demand due to the fact that CO₂ can cause greenhouse effect and also corrosion along the pipeline and at equipment can lowering the heating value of natural gas. In industry most common absorption process is using the amine solution chemical absorbent. However, the use of amine as a solvent to capture CO2 give some disadvantages which need to be stress in order to make efficient process for CO2 capture such as foaming, corrosion of equipment and pipeline. In recent research, they found the new solvents that can perform better than amines in absorbing CO2 which are ionic liquids (ILs). Foaming occurred due to few reasons such as the high gas and the presence of contaminants that enter the process or generated within the process. Since foaming is one of the severe problems in acid-gas removal process, therefore, in this work, two types of ionic liquids are used to study their foaming behavior at different temperature for the removal of CO2. In this study, the ILs that is used were 1-n-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4]) and ln- butyl-3-methylimidazolium chloride ([bmim] [Cl]) and amine used is Nmethyldiethanolamine (MDEA) with temperature variation from 30ºC to 60ºC. 4M of MDEA and 2M of ILs in 100 ml of water of each ILs used was prepared. Carbon dioxide gas is then forced into the solution for 5 minutes prior to start the experiment. A constant nitrogen flow is allowed through the diffuser stone into the solution as the bubbling gas. The height of the foam and the time for foam to break until its original height is recorded as the experimental result. Based on the result, it shows that increasing the temperature has lowering the foam formation. Therefore, less foaming is recorded at temperature 60oC compared to 300C. This is because the surface tension of the solution is decreasing at the same concentration used for MDEA while for [bmim][BF4], it is due to the effect of poor foam stability and reduction of the bulk viscosity of the solution. It has also been found that, [bmim][BF4] solution shows less foaming compared with [bmim][Cl] solution. As a conclusion, it can be said that [bmim][BF4] solution is a very effective ionic liquids since its ability to capture CO2 has been proved by researcher and that it also form less foaming compared to MDEA and [bmim][Cl] solution.